Examination of a Railway Corridor Using a European Transport Model - Berki, Zs.; Cselle, F. (Acta Technica Jaurinensis, 2013)
This paper describes some aspects of building of a European macro level freight transport model, which was part of a three step model system, designed to investigate the feasibility of a freight priority railway corridor bypassing Budapest.